Design of a Semi-Continuous Selective Layer Based on Deposition of UiO-66 Nanoparticles for Nanofiltration - Goji Y. Shangkum; Patchanee Chammingkwan; Dai X. Trinh; Toshiaki Taniike (Membranes, 2018)
Deposition of UiO-66 metal⁻organic framework nanoparticles onto a porous polymer support is a promising approach to designing highly-permeable, size-selective, flexible, and stable membranes for water filtration. In this article, a series of UiO-66 nanoparticles having different particle sizes were synthesized and employed to prepare UiO-66-deposited composite membranes. It was found that the size of the UiO-66 nanoparticles had great influences on the performance of the composite membranes for the filtration of a methylene blue aqueous solution. The deposition of smaller nanoparticles afforded a selective layer having a greater external surface area and narrower interparticle voids. These features made the deposition of smaller nanoparticles more advantageous in terms of the flux and rejection, while the deposition of greater nanoparticles afforded a selective layer more tolerant for fouling. Bimodal composite membranes were prepared by depositing mixed UiO-66 nanoparticles of smaller and bigger sizes. These membranes successfully combined the advantages of nanoparticles of a distinct size.